GEN Z AS MARKET OF WELLNESS PRODUCTS IN YOGA AND MEDITATION: PRACTITIONERS' PERSPECTIVE: GENERASI Z SEBAGAI PASAR PRODUK WELLNESS DALAM YOGA DAN MEDITASI: PERSPEKTIF PRAKTISI - Mahestya, I Gusti Ayu Rayinta; Dari, Komang Nadya Wulan; Everlie, Keane; Baradah, I Gede Abdi Putra (Journal of Applied Science in Tourism Destination, 2025)
This study explores the characteristics of Generation Z in engaging with yoga and meditation practices, examines the role of wellness practitioners in attracting their interest, and proposes strategic approaches for designing appealing and meaningful wellness experiences. Given Generation Z’s growing influence on lifestyle and wellness consumption, understanding their preferences and behavioral patterns is essential for the sustainable development of the wellness industry. This study adopts a qualitative research design, employing multiple data collection methods to enhance data richness and credibility. Data were collected through in-depth and semi-structured interviews with eight yoga and meditation practitioners, complemented by focus group discussions (FGDs) and a review of relevant literature. The findings indicate that Generation Z constitutes a distinctive and strategically important market segment characterized by strong engagement with digital platforms and social media trends. While they demonstrate high levels of curiosity toward wellness activities, they are also easily distracted and tend to seek novel, visually appealing, and socially interactive experiences. Group-based activities, immersive environments, and experiences that integrate aesthetic and technological elements are particularly effective in capturing their interest. The study further reveals that practitioners who are able to adapt their teaching styles, communication strategies, and program designs to align with Generation Z’s digital-oriented lifestyle and values are more likely to attract and retain this demographic as a primary target in the wellness market. These findings offer practical insights for wellness practitioners and industry stakeholders in developing innovative, Gen Z–oriented yoga and meditation experiences that balance authenticity, engagement, and sustainability.